Studi Geolistrik untuk Menentukan Ketebalan dan Komposisi Sedimen di Danau Limboto, Gorontalo - Mamonto, Yusril Mahendra; Yunginger, Raghel; Mursalin, Mursalin; Zainuri, Ahmad; Meidji, Icha Untari; Setiawan, Dewa Gede Eka (Universitas PGRI Semarang, 2025)
This study aims to identify the type and thickness of sediment in Lake Limboto using the Schlumberger configuration geoelectric method. This method was chosen because of its ability to detect resistivity variations that reflect the characteristics of subsurface sediments. The research procedure begins with an initial survey to determine strategic measurement locations, followed by electrode arrangement and resistivity measurements. Data obtained from the measurements were analyzed using geophysical analysis software to produce a resistivity distribution model. The results showed that there were variations in sediment types, including sand, clay, and alluvial soil, as well as varying sediment thicknesses in various locations. These findings are expected to provide useful information for water resource management and mitigation of shallowing problems in Lake Limboto.